Principles in health economics and policy - Olsen, Jan Abel. (Oxford : Oxford University Press, 2010)
Examining the different structures and techniques involved in making decisions about who benefits from those health care resources available in a publicly funded system, this title provides a concise and compact introduction to health economics and policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Medical economics; Medical policy